Legalitas UMKM: Kunci Sukses Pengembangan dan Sinergi Pemasaran UMKM - Ika Suhartanti Darmo; Naik Henokh Parmenas; Donant Alananto Iskandar (BERDAYA: Jurnal Pendidikan dan Pengabdian Kepada Masyarakat, 2021)
Amid the Covid-19 pandemic, entrepreneurs are required to be able to survive and seize business opportunities—the accuracy and strategy needed by every entrepreneur to reduce the impact caused by the pandemic. The community service activities held focused on answering the problems experienced by PKM Partners of the Kalbis Institute of Technology and Business, namely: PKM Partners are MSMEs in East Belitung where MSMEs experience various problems such as product marketing, online sales strategies, access to capital, financial management, raw materials, as well as difficulties in conventionally distributing their business. MSMEs in East Belitung Regency has good potential to be developed. The Covid-19 outbreak poses a threat to MSMEs to develop their businesses. The PKM activities that will be held are focused on answering the problems experienced by PKM partners of the Kalbis Institute of Technology and Business. Keywords: Legality, marketing synergy, micro, small & medium enterprises